병원의 소비자 선호요인분석 : 산부인과를 중심으로 - 서현정 (연세대학교 보건대학원, 1991)
[한글] 이 연구의 목적은 산부인과를 중심으로 산부인과전문병원과 종합병원 및 대학병원에 있어서 소비자들의 병원에 대한 선호요인을 분석하여 중·소 병원의 마케팅전략에 기초자료를 제시하고자 하는 것이었다. 연구결과는 다음과 같다. 1. 일반인의 병원선택 및 선호요인에는 차이가 있었고 산부인과전문병원에 대한선호가 높았다. 산부인과전문병원을 선호하는 요인은 의사의 친절성, 병원의 청결성, 이용의 편리성 등 진료서비스에 관한 항목이었으며 대학병원을 선호하는 요인으로는 병원에 아는 사람(직원)이 있다는 것이었다. 2. 환자의 선호요인에는 차이가 있었고 전반적으로 산부인과전문병원에 대한 선호가 높았다. 산부인과전문병원을 선호하는 요인은 진료수준의 훌륭함, 시설 및 외형의 훌륭함, 친절 및 서비스의 훌륭함 등에 관련된 항목이었고 종합병원 및 대학병원을 선호하는 요인은 접근의 편리함, 타기관에서 후송됨, 응급서비스의 대처능력, 병원에 아는 사람(직원)이 있었음 등이었다. 3. 실제소비자와 잠재소비자의 선호요인에는 차이가 있었고 산부인과전문병원의 경우에는 의술의 신뢰성, 의료시설 및 장비의 현대성, 전통성 및 전문성, 새로운 서비스 등 진료수준의 훌륭함의 항목에서 실제 소비자인 환자의 선호도가 높았다. 종합병원 및 대학병 원의 경우에는 전통성과 전문성, 의사의 친절성, 간호사와 직원의 친절성, 병원건물의 현대성 등에서 실제 소비자인 환자의 선호도가 높았다. 4. 의료제공자가 인지하는 환자의 선호요인과 의료이용자의 선호요인에는 차이가 있었고 산부인과전문병원이나 종합병원 및 대학병원모두에서 환자가 인식하고 있는 선호도 보다 의료기관종사자가 인지하고 있는 환자의 선호도가 높았다. 이상과 같이 소비자의 병원선호요인에 대한 구체적인 분석을 토대로 중·소병원의 경쟁력을 강화시키기 위한 마케팅전략을 수립해야할 것이다. [영문] The purpose of this study was to analyze a consumer preference factor for women's hospitals and general hospitals and to present the basic marketing information for the medium sized hospital. Results were as follows: 1. There were differences in consumer's selection and preference in hospital use. Consumers prefered women's hospitals ; the factors that affected consumer choice of women's hospitals included the kindness of the doctor, neatness of the hospital and convenience for the user. The only reason that people preferred a university hospital was the presence of their aquaintances in the hospital. 2. There were differences in the patient's preference factor, and overall preference for the women's hospital was higher, factors influencing the preference for the women's hospital were the excellence of the level of medicare, quality of the facilities and exterior, and kindness of the employees. Factors influencing preference for the general hospital were the convenience of accessibility, referral from another hospital, capability of emergency services, and the presence of acquaintances in the hospital. 3. There were differences in preferences factors between an actual and potential consumers preferred the women's hospital because of reliability of medical care, modernity of medical facilities, tradition arid specialty, and new services. In the case of a general hospital, tradition and speciality, kindness of the doctors, kindness of the nurses and other employees, modernity of the hospital building ware the preferable factors for the actual consumers. 4. There were differences in preferences between consumers and employees in hospitals. In conclusion, the medium-size hospital should set marketing strategies based on consumer behavior and preferences in order to obtain competitive advantages.
병원행정학과/석사